2008
DOI: 10.1088/0953-2048/21/3/032002
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high flux pinning properties of BaMO3-doped YBa2Cu3O7−xthin films (M = Zr, Sn)

Abstract: We studied the flux pinning properties of BaZrO 3 -doped YBa 2 Cu 3 O 7−x and BaSnO 3 -doped YBa 2 Cu 3 O 7−x films. We found that BaSnO 3 -doped films showed very high global pinning forces, F p , of 28.3 GN m −3 (77 K, B c) and 103 GN m −3 (65 K, B c), twice that of BaZrO 3 -doped films. Transmission electron microscopy analysis showed that, in both films, nanorods of the dopant phase were incorporated. The BaSnO 3 nanorods were nearly straight but the BaZrO 3 nanorods became curved with the increasing film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
194
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(224 citation statements)
references
References 29 publications
25
194
1
Order By: Relevance
“…Although the twin structure is not always visible in TEM images, it is clearly present as seen from the splitting of the XRD peaks 4 and has been seen also in TEM. 32 In addition, the BZO nanorods are usually surrounded by several dislocations in the YBCO lattice, which also act as pinning sites. 16 The role of these dislocations is assumed to be covered by the J c,cd part of Eq.…”
Section: B Pinning In Bzo-doped Ybco Filmsmentioning
confidence: 99%
“…Although the twin structure is not always visible in TEM images, it is clearly present as seen from the splitting of the XRD peaks 4 and has been seen also in TEM. 32 In addition, the BZO nanorods are usually surrounded by several dislocations in the YBCO lattice, which also act as pinning sites. 16 The role of these dislocations is assumed to be covered by the J c,cd part of Eq.…”
Section: B Pinning In Bzo-doped Ybco Filmsmentioning
confidence: 99%
“…YBa 2 Cu 3 O 7−δ (YBCO) still represents one of the best choices for large scale applications of hightemperature superconductors (HTS), such as the fabrication of superconducting coated conductors [1], and the increase of vortex pinning through artificial routes is a field of intense activity [2][3][4][5][6][7]. It was found that BaZrO 3 inclusions in YBCO thin films, for example, significantly enhance vortex pinning for the external magnetic field H parallel to the c axis [2].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Recently, their effectiveness has been observed at low temperatures [12][13][14] However, BZO nanorods are often detrimental to the critical temperature T c , and any such T c loss seriously impedes high temperature applications and blurs pinning mechanism study. 11,[15][16][17] Recently, by modifying the metal-organic chemical vapor deposition (MOCVD) growth process, we successfully incorporated a high density of BZO nanorods into REBCO thin films grown on standard commercial ion-beam assisted deposited (IBAD) templates without any T c loss, a high T c ∼ 91 K persisting up to 20 mol. % Zr-doping.…”
mentioning
confidence: 99%
“…21 F p (H//c) for the 15% Zr-doped film at 77 K is comparable to that of optimized Nb-Ti at 4.2 K, which is ∼16.9 GN/m 3 at ∼5 T. Strikingly, H irr (77 K) ∼14.8 T for the 15% thin film is even higher than the H irr ∼ 11 T of Nb-Ti at 4.2 K. An earlier work using BaSnO 3 and BZO has achieved F p (H//c) > 25 GN/m 3 but peaking at somewhat lower field and without any H irr (T) measurement. 16 J c (H//c) at 4.2 K and H up to 31.2 T of both 7.5 and 15 mol. % Zr-doped films is shown in Figure 4(a).…”
mentioning
confidence: 99%